Lambda point thermodynamics of confined liquid helium: negative surface specific heat - Ferrell, R.A.; Bhattacharjee, J.K. (Физика низких температур, 1998)
We present some theoretical considerations that are relevant to the forthcoming measurements in microgravity of the specific heat of confined liquid helium (the flight experiment «СНЕХ»), Primary attention is devoted to the suppression near the boundaries, the «negative surface specific heat». Above the lambda point, we compute this to lowest order in the c-expansion: below the lambda point our discussion is more restricted.